Features of heart remodeling in patients with obstructive sleep apnea syndrome and its comorbid association with obesity in the context of the senilism concept - T. O. Brodovskaya; O. O. Grishchenko; I. F. Grishina; T. F. Peretolchina (Российский кардиологический журнал)
Aim. To analyze heart remodeling features in with obstructive sleep apnea syndrome and its association with obesity in the context of early cardiac aging.Material and methods. The study included 101 men, 41 patients with obstructive sleep apnea (OSA), 30 comorbid patients with OSA and obesity, the control group consisted of 30 healthy people. The average passport age of the patients was 40,4±6,7 years. Evaluation of OSA was carried out by cardiorespiratory monitoring, structural and functional features of the heart condition were studied using the echocardiography method, the average biological age was calculated.Results. Patients of both studied groups were characterized by structural and geometric rearrangement of the left heart chambers, transformation of physiological ellipsoid model into a spherical (left ventricle (LV) sphericity index 0,64±0,07 in the control group, 1,09±0,03 in the OSA group, 1,01±0,03 in the OSA + obesity group, p<0,05), LV hypertrophy (LV myocardial mass index was 78,1±23,9 in the group of healthy individuals, 98,1±11,4 in the OSA group and 116,0±29,4 in the OSA + obesity group, p<0,01). Systolic function in both study groups was preserved however, a tendency to stress of adaptive remodeling mechanisms was revealed. In addition, diastolic dysfunction was detected in both groups, in OSA group was associated with elasticity of the LV wall decrease, and in the OSA + obesity group, both with a violation of elasticity and an increase in the LV wall stiffness. The biological age of patients with OSA is 14% higher than the passport age, and with the association of OSA and obesity, by 39%.Conclusion. The obtained data prove impact of respiratory sleep disorders at heart remodeling as well as increased biological age. At the same time, the association of OSA with obesity has an additive adverse effect on the remodeling processes and the biological age of patients.